Cirsilineol improves anesthesia/surgery-induced postoperative cognitive dysfunction through attenuating oxidative stress and modulating microglia M1/M2 polarization - Junli Du; Chao Chen; Jie Chen (PeerJ)
Background Cirsilineol is a trimethoxy and dihydroxy flavonoid isolated from plant species such as Artemisia vestita and has a variety of pharmacological properties. This study analyzed whether cirsilineol could prevent postoperative cognitive dysfunction (POCD). Methods A POCD mouse model induced by anesthesia/surgery induction and a cell model established with hydrogen peroxide (H2O2)-induced microglia BV-2 were employed to explore the efficacy of cirsilineol on POCD. The cognition function of the mice were assessed by carrying out behavioral tests (Morris water maze test and Y-maze test). We assessed the activation and polarization status of microglia using immunofluorescence analysis and detected the expression levels of CD86 and CD206 using the quantitative PCR (qPCR). Subsequently, cell viability was determined by CCK-8 assay and apoptosis was assessed using Calcein-AM/PI staining. Meanwhile, superoxide dismutase (SOD) and malondialdehyde (MDA) levels in plasma and cell culture medium were detected using chemiluminescence. Finally, the phosphorylation levels of JAK/STAT signaling pathway-related proteins were analyzed by Western blot. Results Cirsilineol reduced the escape latency and times of crossing island and increased spontaneous alternation (SA) rate, restoring the cognitive dysfunctions of POCD-modeled mice. Meanwhile, POCD elevated CD86 expression and malondialdehyde content and lowered the level of SOD; however, cirsilineol promoted CD206 expression and generation of SOD and inhibited malondialdehyde production. In H2O2-induced microglia BV-2, cirsilineol treatment increased SOD content and suppressed the generation of reactive oxygen species (ROS) and malondialdehyde, modulating microglia M1/M2 polarization and JAK/STAT pathway. Conclusion Cirsilineol prevented against POCD by attenuating oxidative stress and modulating microglia M1/M2 polarization, providing novel insights for the management of POCD.